Estudio en el reconocimiento de plagas, si utilizaran sistemas de drones en La Finca "El Tigrillo", en la parroquia Febres Cordero cantón Babahoyo. - Vargas Mera, Jaime Iván (2022)
In the next article, we will present drones as a technology, thanks to the great advantage of flying over fields and crops, they help collect important information in various agricultural processes and evaluate the state of the soil that is being monitored. With drones, the exact location of your farm can be virtually assessed using high-resolution camera technology and geo-referencing, so you don't have to visit the entire farm directly to see any issues. What is more important is the detection, of future diseases, pests, weeds and weather damage, such as frost and drought, can be identified quickly and effectively. Both ecological and economic efficiency help planting processes, irrigation costs, fertilizers and fumigation.